Decision support systems in the metal casting industry: An academic review of research articles. (2018) - Prasad, Dhrub; Ratna, Sanatan
Abstract: This article offers a complete review of the research articles that are related to the application of decision support and intelligent system with specific reference to metal/dry casting. Data was obtained from 89 articles that were published from 2000 to 2015 in 47 journals. The articles are categorized based upon three different categories based on numbers of impressions, material poured and pressureapplication. They are further classified into 10 subsections. A widespread list of journal articles is identified in this present study that provides relevant information/references for both practitioners and researchers on the application of decision support and intelligent systems to various stages of metal/die casting. In light of the developed classification framework, we identify gaps in extending the use of the decision support and artificial intelligent systems in the industry and suggest potential and applicable research areas for further consideration in this subject area.